PERAN MAHASISWA AKUNTANSI DALAM PENYUSUNAN LAPORAN KEUANGAN SEDERHANA DAN PENINGKATAN KINERJA UMKM HOT PANGSIT NYONYOR - Ritonga, Sally Rahmadani; Laili , Nur Isra; Richmayati , Maya (PUAN INDONESIA, 2025)
This community service program aims to improve financial reporting skills for the owner and employees of HOT PANGSIT NYONYOR, a micro, small, and medium enterprise (MSME) operating in the culinary services sector. The main issue identified is the lack of proper financial record-keeping, which hinders business development and financial management. Assistance was provided collaboratively by students and lecturers through direct mentoring and training in preparing simple financial reports. The results of the program indicate that the MSME was able to independently prepare its own financial reports after the mentoring process. This community service initiative highlights the importance of building financial literacy to support the sustainability of MSMEs.